Initiating how to Work the Maqashid Al-Syariah Theory from Asy-Syahtibi towards the Problem of Thrifting (Trading in Second-Hand Clothes) in Indonesia - Ridho Bawana Jati; Wardah Yuspin (Universitas Muhammadiyah Surakarta, 2023)
This research has the aim of how the maqasid sharia theory works on the problem of thrifting (used clothing trade) in Indonesia. The research method using normative juridical qualitative research is a research method where the research is sourced from legal norms which are obtained from statutory regulations and court decisions. This research approach uses literature studies, official documents and books that are relevant to the problem of this research. This research focuses on Islamic legal regulations regarding Thrifting (Used Clothes Trade) according to Asy-Syahtibi's maqasid sharia theory, while previous research explored more about the law of this object, whether or not it is prohibited for the Thrifting (Used Clothes) Trade. The application of Thrifting (Trading in Used Clothes) is in the theory of maqashid al-syariah where the theory discusses two (2) benefits, namely first, the realization of benefits, goodness and pleasure which is called jaib al-munafi'. Second, avoid evil and damage which is called dar' al-mafasid. Where Thrifting brings about ugliness and chaos or is called dar' al-mafasid because it causes various problems such as many shops selling Thrifting clothes, many garment shops are closed and there is a lot of environmental pollution. Thrifting (trading in used clothes) causes a lot of harm and damage, such as many shops selling thrifted clothes, many garment shops are closed and there is a lot of environmental pollution.